2016
DOI: 10.12740/pp/34810
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive symptoms and physical activity in patients with anorexia nervosa – possible relationships

Abstract: The results show that there is a connection between obsessive-compulsive symptoms and the hyperactivity in AN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
6
0
3
Order By: Relevance
“…Furthermore, we did not find any significant differences when assessing the presence of symptoms such as compulsivity or anxiety traits, measured by SCL-90, in the two groups. With reference to compulsivity, our results are consistent with several studies in which no direct relationship was found between different levels of physical activity and obsessive-compulsiveness as assessed with the SCL-90-R [13,14,57,58]. Conversely, obsessive-compulsiveness was found to be associated with PA in other studies [16,55,58,59], with a hyperactive behavioural profile representing a phenotype more closely linked to OCD than their non-exercising counterparts [55].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we did not find any significant differences when assessing the presence of symptoms such as compulsivity or anxiety traits, measured by SCL-90, in the two groups. With reference to compulsivity, our results are consistent with several studies in which no direct relationship was found between different levels of physical activity and obsessive-compulsiveness as assessed with the SCL-90-R [13,14,57,58]. Conversely, obsessive-compulsiveness was found to be associated with PA in other studies [16,55,58,59], with a hyperactive behavioural profile representing a phenotype more closely linked to OCD than their non-exercising counterparts [55].…”
Section: Discussionsupporting
confidence: 91%
“…Group 1 included only two studies [73,78], which did not find a significant difference between excessive and non-excessive exercisers. However, Blachno et al [78] found that adolescent patients at high risk of obsessive-compulsive disorder reported more intentional physical activities aimed at weight loss than the non-high-risk group.…”
Section: Obsessive-compulsiveness In Anmentioning
confidence: 99%
“…Furthermore, one of the behaviours often associated with eating disorders and body image dissatisfaction is extreme exercising [ 19 ], and this weight management strategy has previously been observed in a South African population [ 12 ]. Therefore, although obesity and physical inactivity tend to go hand-in-hand as already evident in South Africa, normal-weight and underweight individuals experiencing body image dissatisfaction and disordered eating may abnormally increase physical activity levels in order to further control their body mass index (BMI), and thus their body image satisfaction [ 20 , 21 ]. Alternatively, it is possible that if physical inactivity is persisting with body image dissatisfaction, moderate exercise could be encouraged as a means to improve body image satisfaction.…”
Section: Introductionmentioning
confidence: 99%